Circumcision in boys with mild Hemophilia A – the Yogyakarta experience - Pudjo Hagung Widjajanto; Ridwan Tjandra Sugiarto; Sutaryo Sutaryo; Kaiser Ali (Indonesian Pediatric Society, 2007)
Background In boys with hemophilia, there is a risk ofhemorrhage resulting from circumcision. There has been nostandardised management in Indonesia. We report our experiencewith 4 hemophiliac boys who underwent circumcision at Dr.Sardjito General Hospital, Yogyakarta, in south-central Java.Objective To develop a safe, practical and accessible method toprevent bleeding in boys with hemophilia undergoing circumcisionin Indonesia.Methods Written informed consent was obtained from parentsrequesting the procedure. All boys had mild Hemophilia A (VIII:C level >7.8 U/ml) diagnosed at a median age of 4.4 years (range0.75–9 years). Median age at time of circumcision was 7.5 years(range 0.8–12 years).Results There were no intraoperative or post-circumcisionbleeding problem encountered in any of the patients, who weredischarged from hospital three days post-surgery. On follow upeight days and 12 days post-circumcision, they remained free ofcomplications.Conclusion Circumcision can be safely performed in boys withmild Hemophilia A following adequate pre-operative planningand prophylactic therapy. A standardised protocol for theYogyakarta Bleeding Disorders Program. evolving from thisexperience, is being planned.